2017
DOI: 10.1136/archdischild-2016-311548
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic propranolol for prevention of ROP and visual outcome at 1 year (PreROP trial)

Abstract: CTRI/2013/11/004131.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 18 publications
0
19
0
4
Order By: Relevance
“… 20 Intravenous propranolol has been associated with arrhythmias. 21 Intraocular anti-VEGF has been associated with systemic inhibition of VEGF for up to 8 weeks after a single injection. 22 The effects of systemic VEGF inhibition on other developing vascular beds such as the lungs are unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Intravenous propranolol has been associated with arrhythmias. 21 Intraocular anti-VEGF has been associated with systemic inhibition of VEGF for up to 8 weeks after a single injection. 22 The effects of systemic VEGF inhibition on other developing vascular beds such as the lungs are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Further, recent studies demonstrate a possible deleterious refractive outcome of topical propranolol therapy, highlighting the importance of continued study [102]. Conversely, a recent meta-analysis including clinical trial and study data for 461 infants, demonstrated efficacy of oral propranolol for ROP prevention in preterm infants demonstrating a decreased relative risk of severe ROP disease (not complete ROP prevention), supporting prior PreROP trial data [103,104]. However the authors do note that additional well-powered, multinational, randomized control trials reporting on long-term outcomes are needed.…”
Section: Beta Blockersmentioning
confidence: 72%
“…There was a trend toward a lower incidence of ROP (56.8 vs. 68.6%) and less use of laser therapy in the group treated with propranolol, which did not reach statistical significance. 60 After evaluating the incidence of ROP in the propranolol versus the control group, the incidence of stage 1 retinopathy was the same in both groups (27.4%), suggesting that the prophylactic administration of propranolol was not effective in preventing the development of retinopathy. However, a decrease in the incidence of retinopathy was demonstrated in prethreshold stages (stage 2 or stage 3 without plus disease), as shown in other studies.…”
Section: β-Adrenergic Blockers: Propranololmentioning
confidence: 89%
“…During the last 6-year, five studies 48, [57][58][59][60] have been published with the use of oral propranolol as a treatment or prophylaxis and two studies using propranolol drops of ROP. 61,62 One of the first publications by Filippi et al 57 in 2013 evaluated the safety and effectiveness of oral propranolol in 52 preterm infants with ROP.…”
Section: β-Adrenergic Blockers: Propranololmentioning
confidence: 99%
See 1 more Smart Citation